Atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (10th November 2021) - Bacon, Jeffrey R.; Butler, Owen T.; Cairns, Warren R. L.; Cavoura, Olga; Cook, Jennifer M.; Davidson, Christine M.; Mertz-Kraus, Regina
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : In the field of air analysis, highlights within this review period included: a review paper of developments in new personal air samplers for workplace air measurements; a new passive air sampler for Hg 0 ; new filter-based RMs; a new field-deployable carbon analyser for speciation measurements of carbonaceous aerosols and advances in the measurement of RCS using vibrational spectroscopic techniques. The maturity of AAS methods for the analysis of waters was highlighted this year by the lack of significant developments. All the novelty was in sample preparation as reflected in Tables 1 and 2 . The tables also reflect the large interest in the use of graphene oxide as a solid phase for preconcentration and the continued use of magnetic nanoparticles. There are now enough methods and application to warrant the inclusion of the analysis of nanoparticles as a separate section rather than as a subsection in speciation. This trend is set to continue as instrumental improvements allow lower size LODs and the determination of lower particle numbers. Notable advances in the analysis of soils and plants included work on the preparation of new RMs as alternatives to NIST soil SRMs that are now in short supply. There was increased interest in the development of miniaturised AES instruments with the potential for field deployment. In the analysis of soil by LIBS, more studies included some form of external validation e.g. comparison with results of an established analytical method, which is most welcome. The availability of well-characterised matrix-matched reference materials continues to be a limitation in the production of high-quality geoanalytical data, particularly when exploring the fine structure of geological materials by microanalytical techniques such as LA-ICP-MS and SIMS. It is heartening to see that many of the researchers working in this area appreciate the importance of making new RMs available to the wider geochemical community. Although the development of portable LIBS systems continues to attract much interest, the current generation of instruments do not appear to be able to match the capabilities of techniques like pXRFS, particularly for the quantification of minor and trace elements in geological settings. Some of the LIBS calibration issues highlighted are reminiscent of those encountered in the early days of pXRFS and should be overcome in time. Many of the reported improvements to in situ measurements of isotope ratios were in support of geochronological studies. Likely future trends include the increased use of imaging in U–Pb geochronology given that LA-ICP-QMS mapping is now capable of acquiring all the required compositional and U–Pb age information at high-spatial resolution.